Use of e-plastic waste in bituminous pavements - Lakshmi Murugan (Građevinar, 2018)
This paper presents the research conducted on the samples of traditional asphalt mixes and asphalt mixes with plastic granules as replacement for coarse aggregate. Marshall stability parameters of these mixes are compared to determine an optimum proportion of plastic granules. The objective was to determine whether plastic components obtained by e-waste recycling can be used in pavement structures. The research was conducted in the scope of the plan for accountable management of increasingly growing quantities of e-waste.